Anti‐Tuberculosis Evaluation and Conformational Study of N‐Acylhydrazones Containing the Thiophene Nucleus. Issue 6 (10th March 2014) - Cardoso, Laura N. F.; Bispo, Marcelle L. F.; Kaiser, Carlos R.; Wardell, James L.; Wardell, Solange M. S. V.; Lourenço, Maria C. S.; Bezerra, Flávio A. F. M.; Soares, Rodrigo P. P.; Rocha, Marcele N.; de Souza, Marcus V. N.
<x xml:space="preserve">Abstract</x> A series of N‐acylhydrazonyl‐thienyl derivatives (compounds 2 and 3), mainly of the type 2‐(aryl‐CHNNHCOCH2)‐thiene (2: aryl = substituted‐phenyl; 3: aryl = heteroaryl) were evaluated against Mycobacterium tuberculosis. Particularly active compound was 3 (heteroaryl = 5‐nitrothien‐2‐yl or 5‐nitrofuran‐2‐yl) with MIC values of 8.5 and 9.0 μM, respectively. Moderately active compounds were compound 3 (heteroaryl = pyridin‐2‐yl) and compound 2 containing aryl = 2‐ or 4‐hydroxyphenyl groups, with MIC values between 170 and 408 μM. Compound 2 containing OMe, H, F, Cl, Br, CN, and NO2 substituents and compound 3 (heteroaryl = furan‐2‐yl, thien‐2‐yl, pyrrol‐2‐yl, imidazol‐2‐yl, pyridin‐3‐yl, and pyridin‐4‐yl) were all inactive. Clearly, there is no correlation of activity with the electronic effects of the substituents. The activities suggest different modes of biological action of the compounds having nitro‐heteroaryl groups, on the one hand, and the 2‐hydroxyphenyl or pyridin‐2‐yl substituents, on the other hand. Compounds having 2‐ or 4‐hydroxyphenyl, 2‐hydroxy‐5‐nitrophenyl, or 4‐hydroxy‐3‐chlorophenyl were less cytotoxic than ethambutol. It is important to notice that compound 3 (aryl = 5‐NO2‐furan‐2‐yl) exhibited a promising therapeutic index (TI = 1093.90), with a value 4.4 less than that of ethambutol. Compounds 2 and 3 exist in DMSO or MeOD solutions as mixtures of EC(O)N/ECN and ZC(O)N/ECN conformers.